2022
DOI: 10.1021/acsami.2c11369
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Work Function and Acoustic Impedance Mismatch for Improved Thermoelectric Performance in GeTe-WC Composite

Abstract: The preparation of composite materials is a promising methodology for concurrent optimization of electrical and thermal transport properties for improved thermoelectric (TE) performance. This study demonstrates how the acoustic impedance mismatch (AIM) and the work function of components decouple the TE parameters to achieve enhanced TE performance of the (1-z)Ge 0.87 Mn 0.05 Sb 0.08 Te-(z)WC composite. The simultaneous increase in the electrical conductivity (σ) and Seebeck coefficient (α) with WC (tungsten c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Single-phase alloys have been well studied with five times the number of publications on multiphase/composite TE materials, but investigating composites is one of the most viable strategies to enhance thermoelectric performance by designing new materials . Constructing suitable nanostructures to optimize the electronic and thermal transport properties simultaneously is widely used in the GeTe-based system, such as superlattices, , stacking faults, dislocation arrays, in situ nanoprecipitates, , and ex situ nanophases. …”
Section: Introductionmentioning
confidence: 99%
“…Single-phase alloys have been well studied with five times the number of publications on multiphase/composite TE materials, but investigating composites is one of the most viable strategies to enhance thermoelectric performance by designing new materials . Constructing suitable nanostructures to optimize the electronic and thermal transport properties simultaneously is widely used in the GeTe-based system, such as superlattices, , stacking faults, dislocation arrays, in situ nanoprecipitates, , and ex situ nanophases. …”
Section: Introductionmentioning
confidence: 99%
“…However, thermoelectric performance of thin film counterpart does not align with their bulk form due to different fabrication process lead to dissimilar electronic and thermal transport properties . To enhance the thermoelectric properties of thin films, developing metal–semiconductor (M–Sc)-based composites offers a viable approach, extensively researched in the bulk forms of various thermoelectric materials. These composites effectively boost the electrical conduction through mechanisms such as carrier channeling, and carrier injection simultaneously suppresses phonon conduction by enhancing interfacial phonon scattering to achieve enhanced thermoelectric performance. ,, The influence of the metallic phase on σ is contingent upon the band structure of the matrix, the potential energy barrier at the interface between the two phases, and the electrical and thermal transport properties of the metallic phase. Also, the morphology, amount, and physical characteristics of the guest phase play a critical role in determining the resulting thermoelectric transport properties. , Previous studies had demonstrated the effect of metallic nanostructures in TE materials like (Bi,Sb) 2 (Te,Se) 3 , CoSb 3 , and MnSi 1.787 Al 0.0138 , where the selection of metallic inclusions with distinct work functions provides the perspective of a tunable barrier at the interface, promoting the electronic transport to tailor the TE properties.…”
Section: Introductionmentioning
confidence: 99%
“…Doping has been extensively studied in literature with the aim of reducing the presence of toxic elements and enhancing the properties of compounds. [50][51][52][53] Therefore, in this study, we have substituted Pb with Sn and Ge in the MAPbI 3 perovskite. Another method for reducing Pb content is by introducing Pb-vacancies in the compound, however, it is worth noting that such vacancies are not stable.…”
Section: Introductionmentioning
confidence: 99%